Acute Promyelocytic Leukemia (APML) in A Four Year Old Child: A Case Report - Sonia, Sheikh Farjana; Choudhury, Ahmed Murtaza (Dhaka Shishu (Children) Hospital Journal, 2021)
Abstract not available DS (Child) H J 2020; 36(2): 166-169